Hypertension, smoking, and preexistence of multiple cardiac risk factors correlate with carfilzomib-induced cardiovascular adverse events in a racially diverse population - Doran, Stacey; Mysore, Manu; Kassaian, Seyed Ebrahim; Kotloff, Ethan; Kamangar, Farin; Emadi, Ashkan; Apata, Jummai; Barr, Brian (Frontiers in Cardiovascular Medicine, 2023)
Background: Use of the proteasome inhibitor carfilzomib has become a standard of care in patients with relapsed/refractory multiple myeloma. An association between carfilzomib and cardiovascular adverse events has been well documented, but this had not been investigated in a racially diverse population. Black patients in particular are underrepresented in the reported outcomes of treatment with carfilzomib. Objective: The purpose of this study was to identify risk factors for carfilzomib-associated cardiovascular events in a diverse, single-center population. Methods: We conducted a retrospective review of 161 patients with multiple myeloma treated with carfilzomib between 2011 to 2020 at the University of Maryland Medical Center. Over half (86) were Black patients, with the remainder (75) being White patients. We did a multivariate analysis to determine risk factors for developing cardiovascular events during treatment with carfilzomib. Results: There was no statistically significant association with cardiotoxicity and race, gender, or age at first dose of carfilzomib. In multivariable analysis, patients with history of hypertension had a higher risk of cardiotoxicity [adjusted odds ratio (OR), 2.5; 95% CI, 1.1-5.9; P=0.03] as did those with a history of smoking [OR, 2.8; 95% CI, 1.3-6.4; P=0.01]. Conclusions: Here we report the largest cohort of Black patients treated with carfilzomib as yet reported. The results of this single center retrospective study show history of hypertension and smoking are associated with carfilzomib associated cardiotoxicity in a diverse patient population. There is a need for well-designed prospective studies enrolling a diverse population to investigate potential interventions to prevent carfilzomib-associated cardiotoxicity.